Do the circulating Pre‐S/S quasispecies influence hepatitis B virus surface antigen levels in the HBeAg negative phase of HBV infection?. Issue 12 (11th May 2020) - Cavallone, Daniela; Ricco, Gabriele; Oliveri, Filippo; Colombatto, Piero; Moriconi, Francesco; Coco, Barbara; Romagnoli, Veronica; Salvati, Antonio; Surace, Lidia; Bonino, Ferruccio; Brunetto, Maurizia Rossana
Summary: Background: Virus, host factors and their interplay influence Hepatitis B surface Antigen serum levels during Hepatitis B Virus (HBV) infection course and treatment. Aim: To study the Pre‐S/S circulating quasispecies in a cohort of untreated, HBeAg negative, genotype‐D, HBsAg carriers. Methods: We studied 260 carriers: 71 with HBeAg negative infection (ENI; HBV‐DNA ≤2000 IU/mL); 42 Grey Zone (GZ; HBV‐DNA ≤20 000 IU/mL); 82 chronic hepatitis (CH) and 65 cirrhosis (CI) (HBV‐DNA > 20 000 IU/mL). Population sequencing was applied to identify Pre‐S/S gene mutations responsible for any amino acid substitution or potential biological/antigenic implications (M‐muts) on HBsAg. Results: HBsAg serum levels were lower in ENI + GZ than in CH + CI (2.61 [−1.10/4.06] vs 3.62 [2.41/4.92] log10 IU/mL, P  < 0.001) and in CI than CH (3.48 [2.41/4.38] vs 3.66 [2.57/4.92] log10 IU/mL, P  < 0.001). M‐muts were found in 73 (28.1%) cases: 5 (7.0%) ENI, 3 (7.1%) GZ, 26 (31.7%) CH, 39 (60.0%) CI ( P  < 0.001) and mostly in Pre‐S2 (17.6%) than Pre‐S1 (5.8%) and Small‐S (10.8%; P  < 0.001). Overall HBsAg serum levels were higher in carriers with M‐muts (3.56 [0.95/4.38] vs 3.17 [−1.10/4.92] log10 IU/mL, P  < 0.001), but comparable in carriers with or without M‐mut when considering separately ENI + GZ (2.84 [0.95/3.89] vs 2.61 [−1.10/4.06] log10 IU/mL, P  = 0.330] and CH + CI (3.57 [2.67/4.38] vs 3.63 [2.41/4.92] log10 IU/mL, P  = 0.37). Infection phase ( β : 0.422, P  < 0.001), age ( β : −0.260, P  < 0.001), ALT ( β : −0.103, P  = 0.045), liver stiffness ( β : −0.118, P  = 0.039) and HBV‐DNA ( β : 0.384, P  < 0.001), but not M‐mut were independently associated with HBsAg serum levels. Conclusions: In HBeAg negative, genotype‐D, carriers Pre‐S/S heterogeneity increases with severity of liver disease, but does not influence HBsAg serum levels, that in low viraemic carriers are associated with an effective control of HBV.